Surgeons and HIV: a South African study - Szabo, Christopher Paul (My University, 2008)
A contentious area of clinical practice in the discipline of surgery, with ethical implications, relates to disclosure of clinician HIV status to patients, specifically where exposure prone procedures, performed in a confined body space using sharp instruments without full vision of the operative area, carrying a technical risk of blood borne pathogen transmission are being performed by HIV positive surgeons. Within the context of patient informed consent, it has been proposed that surgeons who are HIV positive make their status known to patients on whom they would perform such procedures. Failing which it is proposed that surgeons who are HIV positive should refrain from such procedures. It has been counterargued that such disclosure is an infringement on clinician privacy and that curtailing the scope of practice is prejudicial to both surgeon and patient. The former in terms of employment prospects and the latter based on the lack of data supporting a significant risk of clinician to patient transmission with a resultant unnecessary loss of surgical skills. Existing recommendations appear to be informed more by sentiment than science and are thus potentially unsatisfactory, more so in that they do not seem to confer benefit to either patients or clinicians. Further, whilst such policies emanate from developed countries they may not address the clinical realities or sentiment of the South African situation. Where such policies do exist, it is not clear to what extent the recommendations accord with clinician views. Against this background the current study surveyed views of practicing South African surgeons regarding aspects of this issue i.e. HIV and surgeons. Some of the salient findings included the view that a patient centred approach requiring HIV status disclosure to patients would be discriminatory to surgeons whilst not clearly of benefit to patients. Further that HIV positive surgeons should determine their own scope of practice. Certainly it appears that patient centered approaches and restrictive policies, related to this issue, do not appear to accord with clinician sentiment. In the absence of any comparable data either locally or internationally, the current study provides a preliminary indication of clinician views with implications for the development of locally relevant guidelines.
Keywords: surgeons; HIV; South Africa